PENGARUH PROFITABILITAS DAN LEVERAGE TERHADAP RETURN SAHAM PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2015-2019 - Elin Afriani; Irdha Yusra (Jurnal Pendidikan Ekonomi, 2021)
ABSTRACTThis research is meant to test influence of profitability and Leverage on stock returns. The population is all companies which are listed in Indonesia Stock Exchange in 2015-2019 periods. The sample collection technique has been carried out by using purposive sampling method with 134 companies have been selected as samples. The analytical method used is regression analysis of panel data with the help of application E-Views 8. The result indicated that the profitability have positive and significant influence on Stock Return in Indonesia, and Leverage have negative and significant influence on Stock Return.